Manajemen Perianestesi dengan Subarachnoid Block dan Sedasi pada Pasien Sectio Caesarea Emergency dengan Plasenta Previa dan Hipertiroid: Studi Kasus - Dani, Dwi Darmawan; Agepho, Al Farouk Ozan; Wibowo, Ratu Laraswati Sekar; Yudha, Magenda Bisma; Muti, Refa Teja (Pustaka Galeri Mandiri, 2026)
Emergency cesarean section in patients with placenta previa and hyperthyroidism presents significant anesthetic challenges due to the risk of massive hemorrhage and thyroid crisis. This case report describes the perioperative anesthetic management of a 31-year-old woman, G3P2A0, with complete placenta previa and uncontrolled hyperthyroidism who underwent emergency cesarean section. The patient presented with active vaginal bleeding at 39 weeks gestation. Laboratory findings revealed anemia (Hb 11.6 g/dL) and hyperthyroid state (TSH 0.10 mIU/L, FT4 3.24 ng/dL). Subarachnoid block was performed at L4-L5 level using levobupivacaine 12.5 mg combined with intrathecal morphine 70 mcg, achieving sensory block up to T6 dermatome. Light sedation with midazolam 3 mg and propofol 4 mg was administered intravenously after delivery. Intraoperative hypotension (90/61 mmHg) was managed with fluid resuscitation and ephedrine 10 mg IV, resulting in stable hemodynamics. The procedure was completed successfully without major complications. Postoperatively, the patient recovered well with Bromage score improving from 3 to 2 and Aldrete score reaching 9. This case demonstrates that subarachnoid block combined with light sedation provides safe and effective anesthetic management for emergency cesarean section in patients with placenta previa and uncontrolled hyperthyroidism, avoiding the risk of thyroid storm associated with general anesthesia